Controlling of the Structural Characteristics of ZnO Nanomaterials by Reaction Pressure and Reaction Time - Kati, Nida; Ozan, Sermin; Yildiz, Tulay; Korkmaz, Ayca (Int Inst Science Sintering (I I S S), 2022)
The most significant parameters affecting particle size and morphology in nanoscale powder production are the working temperature and working time. The reduction in size leads to the addition of new electrical, mechanical, chemical and optical properties to the materials. The properties of nano ZnO are of special importance due to its multi-dimensional applications in the fields of industry, cosmetics, electronics, etc. Zinc oxide (ZnO) with various morphologies was synthesized by hydrothermal method at different temperatures (140, 180 and 220 degrees C) and different times (12, 18 and 24 h). The samples were characterized by SEM EDX, XRD and UV-vis techniques. SEM and EDX findings show that especially ZnO nanostructures have developed. The pattern of the XRD showed that the sample was well crystallized in a structure of hexagonal wurtzite. The energy band gap values samples synthesized at different parameters were found to be 3.07, 3.10, 3.19, 3.17 and 3.13 eV, respectively.
Keywords: ZnO; Hydrothermal synthesize; Morphology; XRD; Band gap